The emperor's writing : memories of Akbar the Great - Collier, Dirk (New Delhi Amaryllis, 2011)
A compilation of true stories written by teenagers, and by adults writing about their teenage years, focusing on teen relationships with parents, friends, crushes, boyfriends and girlfriends.
Includes bibliographical references